Management economics in a large retail organization - William Stanley Siebert; Nikolay Zubanov (Institute for the Study of Labor (IZA), 2008)
We study the impact of and reward to middle management ability using data from 245 stores of a nationwide retailer. The company scores six broad areas of management practice, the most important of which turns out to be commercial awareness, where able managers raise labour productivity by 17% compared to less able. We show that the managers' incentive scheme is implicitly an insurance one, with managers taking a share in deviations of actual sales from expected. At the same time, abler managers do not receive higher pay all else equal, which implies that middle management ability is not fully tradable.
urn:nbn:de:101:1-20080825222
Keywords: D21; 330; Management; firm behaviour; business economics; productivity; compensation methods; Mittleres Management; Kompetenz; Vergütungssystem; Arbeitsproduktivität; Einzelhandel; Großbritannien